INFORMATION TECHNOLOGY IN EVERYDAY LIFE OF THE PORTUGUESE - BULKA, Beata; Justyna, KOS (Trends in education, 2010)
The article presents the results of research on Information Technology in everyday life of the Portuguese. The research was conducted in winter and spring of 2009 among the working population with high level of education. People were selected through a random way. The research were conducted among 160 people in Portugal.
Keywords: Informational Technology; Portuguese; working population.